Asymmetric Organocatalysis Revisited: Taming Hydrindanes with Jørgensen–Hayashi Catalyst - Stöckl, Yannick; Frey, Wolfgang; Lang, Johannes; Claasen, Birgit; Baro, Angelika; Laschat, Sabine (Synthesis, 2019)
The organocatalytic Michael reaction of easily available 1-cyclopentene-1-carbaldehyde and 1,3-dicarbonyl compounds led to cyclopentanecarbaldehydes on a gram scale with low catalyst loading (2 mol%) and high enantioselectivity. The synthetic potential of 4-acylhexahydroindenones from intramolecular aldol condensation was demonstrated by Diels–Alder reaction to a tetracyclic derivative with seven stereogenic centers. The diastereofacial preference of the tetracyclic product was confirmed by DFT calculations. The described reaction sequence is characterized by few redox-economic steps and high degree of molecular complexity.
Keywords: organocatalysis; hydrindane; Jørgensen–Hayashi catalyst; Michael addition; aldol condensation; Diels–Alder reaction